The Algorithmic Lifeline: The Role of AI in Advancing Suicide Risk Prediction and Prevention - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The global public health crisis of suicide presents a profound challenge to healthcare systems worldwide. Traditional methods of risk assessment, often relyi...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care